PENGARUH INTERNAL LOCUS OF CONTROL TERHADAP MOTIVASI BERPRESTASI PADA MATA PELAJARAN EKONOMI SISWA KELAS XI SMAN 2 MANDAU - Nofia, Imelda Nofia Imelda; Nas, Syakdanur Nas Syakdanur; Trisnawati, Feny Trisnawati Feny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : There is a difference between expectations and reality occurred in class XI IPS in SMAN 2 Mandau where the lack of student achievement motivation, especially on economic subjects. The purpose of this study was to determine and analyze how much influence the internal locus of control on achievement motivation on economic subjects XI grade students of SMAN 2 Mandau. The method used is descriptive quantitative. The population is all students of class XI SMAN 2 Saber totaling 147 students with a sample of 60 students. Based on the results of data analysis is concluded that in mind the significant value on the table coeffisients 0,000 less than the critical value of 0.1. Then obtained 0,000 < 0.1 and this result shows that the Internal Locus Of Control (ILOC) significantly affects Achievement Motivation (MB) in class XI students majoring in social studies at SMAN 2 Mandau the academic year 2014/2015. Judging from R Square of 0.589, this shows that the independent variables used in this study could affect the dependent variable by 58, 9%. Thus it can be said that the ability of the independent variables affect the dependent variable is strong. Based on the regression coefficient if ILOC increased by 1%, the achievement motivation will also increase by 0845 or 84.5%. Coefficient is positive, it means there is a positive relationship between the MB with ILOC, the rise ILOC then the ride anyway Achievement Motivation.Key Words : Achievement Motivation, internal locus of control